2009
DOI: 10.1016/j.proci.2008.06.141
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigations of a low-swirl injector with H2 and CH4 at gas turbine conditions

Abstract: Laboratory experiments were conducted at gas turbine and atmospheric conditions (0.101 < P 0 < 0.810 MPa, 298 < T 0 < 580K, 18 < U 0 < 60 m/s) to characterize the overall behaviors and emissions of the turbulent premixed flames produced by a low-swirl injector (LSI) for gas turbines. The objective was to investigate the effects of hydrogen on the combustion processes for the adaptation to gas turbines in an IGCC power plant. The experiments at high pressures and temperatures showed that the LSI can operate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 20 publications
7
84
0
1
Order By: Relevance
“…A large recirculation (indicated by negative values of u z /U o ) is also formed. The trends of these profiles are consistent with those measured previously on larger LSBs (Cheng, 2009). Because swirler SW4 has a higher swirler number than other LSB developed for commercial use (attained by have a larger blockage of the center plate), the flame position is close to the burner exit.…”
Section: Flame Flow Field Using Pivsupporting
confidence: 87%
See 1 more Smart Citation
“…A large recirculation (indicated by negative values of u z /U o ) is also formed. The trends of these profiles are consistent with those measured previously on larger LSBs (Cheng, 2009). Because swirler SW4 has a higher swirler number than other LSB developed for commercial use (attained by have a larger blockage of the center plate), the flame position is close to the burner exit.…”
Section: Flame Flow Field Using Pivsupporting
confidence: 87%
“…At higher heat outputs (greater than 38 kBTU/hr), the velocity profiles are more consistent, as the turbulent divergent flow is fully developed and assumes similarity features reported by Cheng et al (2009). A large recirculation (indicated by negative values of u z /U o ) is also formed.…”
Section: Flame Flow Field Using Pivsupporting
confidence: 66%
“…Burning under lean conditions reduces the exhaust gas temperatures, and consequently, thermal NOx emissions. Low-swirl burner technology, introduced by [1] as a tool for studying the fundamental properties of lean premixed turbulent flames has proven to be an effective stabilization mechanism for a wide range of fuels, see [2] and [3]. However, high-swirl injectors, often used in gas turbines, can generate much higher levels of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, laboratory tests have shown that the fundamental operating principle of the LSI provides not only fuel flexibility but also smooth transitions between various fuels. Laboratory results obtained at simulated gas turbine conditions using simulated coal-based syngases [3] and natural gas and hydrogen blended fuels [4] show that the LSI does not require any hardware change to operate with these different fuels.…”
Section: Background and Objectivementioning
confidence: 99%